From Punch Cards to Modern Corpora: Quantification and Statistics as Tools for Literary Studies? - Zmelik, Richard (Bohemica Olomucensia, 2016)
Traditionally, methods of quantitative and corpus analysis have chiefly been applied in linguistics. Only in recent years have (mainly foreign) studies tested their possibilities in the sphere of literary studies. The main purpose of such an approach is to provide literary studies with an exact tool, one based on formally analysed verbal material and not burdened with subjective introspective aspects. The principle of quantitative-corpus analysis does not only comprise the schematised taxonomy of a verbal corpus - it also presupposes its categorical statistical analysis, which is capable of manifesting (representing) absolute structural values and qualities.
Keywords: Quantitative Analysis; Corpus Analysis; Statistical Analysis; Taxonomy; Verbal Corpus; Literary Studies